Paolo Sylos Labini, 1920-2005 - Roncaglia, Alessandro (PSL Quarterly Review, 2012)
The paper outlines the intellectual biography of Paolo Sylos Labini, a great economist with strong civic ideals. After recalling his education (in Rome, then at Harvard with Schumpeter and at Cambridge with Robertson), the paper illustrates his contributions in a variety of fields, ranging from economic policy and applied analysis (including the first econometric model of the Italian economy) to the history of economic thought and the analysis of technical progress, from social classes (with a stress on the role of the middle classes) to underdevelopment, and especially to oligopoly theory, conceived as a general theory of market forms, based on the notion of barriers to entry in an industry. Sylos Labini's political involvement and his strong civic values are also briefly illustrated. JEL Codes: B32